THE ROLE OF TECHNOLOGY IN ENHANCING ENGLISH SPEAKING SKILLS A LITERATURE OVERVIEW - Yohanis Tarukallo; Wira Jaya Hartono; Irsan Bertinus Tondowala; Deni Melyati; Mohammad Iskandar Dzulkurnain; Mike Nurmalia Sari (EDU RESEARCH, 2024)
This literature review explores the role of technology in enhancing English speaking skills, focusing on how various technological tools such as gamification, speech recognition, and online collaboration align with the principles of Communicative Language Teaching (CLT). The review discusses the effectiveness of these tools in improving fluency, accuracy, and confidence in English language learners, while also addressing the challenges faced by both learners and educators in integrating technology into speaking-focused instruction. Furthermore, it examines how these technologies support the core CLT principle of authentic communication. The review concludes with a discussion of the pedagogical implications and future directions for the integration of technology in English speaking instruction, highlighting the importance of balancing technology use with traditional communicative practices for optimal learner outcomes.